1998
DOI: 10.1002/(sici)1096-9861(19981026)400:3<317::aid-cne3>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Histaminergic neurons in the sheep diencephalon

Abstract: The distribution of histaminergic neurons in the sheep brain was studied by immunohistochemistry by using antibodies raised against histamine. For the first time in this species, the presence of histamine-immunoreactive neurons was described in the caudal diencephalon, around the mammillary bodies, and in the tuberomammillary area. The general pattern of distribution of these neurons was similar to that described previously in other species, i.e., rodents and humans. The distribution in the five neuronal group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…The CP, located at different sites of the third (3V), fourth (4V) and lateral ventricles (LV; Wolburg and Paulus, 2010), is the site of production of the cerebrospinal fluid (CSF), which transports essential molecules throughout the nervous system. The CP contains receptors for 5HT (Watson et al, 1995) and HA (Crook et al, 1986), and both neurotransmitters influence metabolism in this area (Crook et al, 1984, Watson et al, 1995); the route may be through their direct release into the CSF as suggested by studies that report the presence of histaminergic (Ericson et al, 1987, Tillet et al, 1998) and serotonergic (Lorez and Richards, 1973, Chan-Palay, 1976) axons or dendrites in close proximity to the ventricles.…”
Section: Introductionmentioning
confidence: 99%
“…The CP, located at different sites of the third (3V), fourth (4V) and lateral ventricles (LV; Wolburg and Paulus, 2010), is the site of production of the cerebrospinal fluid (CSF), which transports essential molecules throughout the nervous system. The CP contains receptors for 5HT (Watson et al, 1995) and HA (Crook et al, 1986), and both neurotransmitters influence metabolism in this area (Crook et al, 1984, Watson et al, 1995); the route may be through their direct release into the CSF as suggested by studies that report the presence of histaminergic (Ericson et al, 1987, Tillet et al, 1998) and serotonergic (Lorez and Richards, 1973, Chan-Palay, 1976) axons or dendrites in close proximity to the ventricles.…”
Section: Introductionmentioning
confidence: 99%
“…The role of thalamus as the ‘cross of multiple brain circuits’ and ‘the central switchboard’ in conjunction with the fundamental modulating role of histamine and the involvement of both in various brain functions raise interesting questions on the relationship between these two. Histaminergic neurons are located exclusively in the posterior hypothalamic tuberomamillary nucleus in all mammals studied so far (Panula et al ., 1984; Steinbusch & Mulder, 1984; Watanabe et al ., 1984; Airaksinen & Panula, 1988; Airaksinen et al ., 1989, 1991; Tillet et al ., 1998; Sallmén et al ., 1999), and the efferent fibres reach almost all parts of the brain (Wahlestedt et al ., 1986; Airaksinen & Panula, 1988; Panula et al ., 1989; Inagaki et al ., 1990). A small group of histaminergic fibres was found to enter the thalamus and terminate selectively in some thalamic nuclei of rodents (Airaksinen & Panula, 1988; Airaksinen et al ., 1989; Panula et al ., 1989) and cats (Uhlrich et al ., 1993).…”
Section: Introductionmentioning
confidence: 99%
“…An immunohistochemical method using an anti-HIS antibody or an anti-L-histidine decarboxylase antibody enabled the morphological identification of HIS neurons [17,25] which have been previously reported in various mammals [4,11,15,18,21,22,27]. From a comparative morphological viewpoint, we have reported the intracerebral distribution of monoaminergic neurons in vertebrates, including the shrew (Suncus murinus) of the Insectivora order [6].…”
Section: Introductionmentioning
confidence: 81%